P39 Real world experience of using bezafibrate for PBC. (28th September 2020) - Jessa, Fatema; Halliday, Neil; Shah, Tina; Thorburn, Douglas
Abstract : Primary Biliary Cholangitis (PBC) is a rare autoimmune condition with an incidence of 20–40 cases per 100, 000. Levels of alkaline phosphatase (ALP) can be used as a surrogate marker of clinical response to pharmacotherapy. Ursodeoxycholic acid (UDCA) is first line therapy and Obeticholic acid (OCA) is second line therapy for those intolerant or unresponsive to UDCA. Bezafibrate (BZF) is an unlicensed therapy available for those intolerant or unresponsive to UDCA or OCA. The aim of this analysis is to investigate effectiveness and safety of BZF in a real world, specialist centre setting. All patients dispensed BZF from July 2019 to June 2020 from Royal Free London Hospital were included. Using dispensing and clinical records, demographic, pharmacological and clinical data were collated. 24 patients were treated with BZF. 1 patient was excluded due to being treated with plasma exchange making her laboratory data uninterpretable. All patients were female with a median age of 56 years and as a group, had elevated median liver stiffness of 10.2kPa. The table 1 below shows the relevant outcomes. Biochemical response is presented in groups treated with BZF and UDCA, combination of BZF, OCA and UDCA or BZF alone. Our data demonstrate that over a median of 2 months follow-up, BZF is well tolerated with only 3/23(13%) stopping therapy. BZF was effective especially used as triple therapy, as shown by at least 15% reduction in ALP in 18/23(78%) and ALP<1.67xULN in 15/23(65%) even at this very early time point. No patients died or experienced complications of hepatic decompensation.